Analysis of the human body through drawing: Plastic modelization through observation - González Vázquez, Margarita (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The study of the human body through sketching allows the student of Fine Arts to delve into the complex perceptual, cognitive and procedural processes of drawing, since this practice favors both the analysis of the human body and the assimilation of strategies to assume the deep relationship that is established between the artist and what he/she observes, understands and materializes in the drawing itself. For this reason, this paper analyzes the factors involved in this situation and offers a number of strategies that facilitate the acquisition of the necessary skills for it after implementing an exercise program for this purpose.